Handover Decision Mechanism in Interworking Technologies Using Radial Basis Functions - Payal Mahajan; Kuldeep Singh; Hardeep Kaur (IAES International Journal of Artificial Intelligence (IJ-AI), 2014)
As a mobile user travels between radio networks, a handover mechanism is required to vary its radio connection. The persistence of a call is one of the major quality measurements in wireless cellular networks. Handover mechanism permits a cellular network to offer such a facility by again allocating an ongoing call from one base station to another base station. To achieve handover neural network techniques can be used. In this paper, a handover decision mechanism is proposed using Radial Basis function (RBF) of neural networks.